Analysis of the tax pilot phase strategy and its impact on the tax price in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the tax policy strategy adopted in Iraq after the change of the tax system in 2003 and beyond, and then make a comparison of the two strategies on corporate data whether they are charged with progressive tax rates and after the change of the system as the tax rates became fixed, and then indicate the changes In the tax proceeds, and knowing the imensions of the approved tax policy, is it a tax reform strategy or a strategy to attract investments.The research started from the problem of exposure of the Iraqi tax system to several changes, as this led to a reflection on the technical organization of taxes, in terms of the tax rate.The descriptive analytical approach was chosen to study the actual reality of the data, and in the light of the analyzes and results achieved, the researcher concluded that the application of this mechanism for progressive tax rates led to an increase in the rate of tax revenue, in contrast to what has been implemented with regard to the fixed tax rate, and this is not what was claimed as a tax reform strategy, but rather It was a foreign investment entry strategy. The research based its most important recommendations on reconsidering the corporate tax rate and raising the tax rate in proportion to the increase in tax revenues.